Silent Leaders in the Workplace: Forms of Leadership Silence, Attributions of Leadership Silence, and Accuracy of Attributions. (October 2021) - Chang, Tree; Chou, Shih Yung; Han, Bo
Building upon the extant leadership research, we explore the phenomenon of leaders' intentionally withholding of relevant information to subordinates. In particular, we conceptualize leadership silence and propose three distinct forms of leadership silence, including safeguarding silence, undermining silence, and disengaging silence. We also incorporate attribution theory and show how subordinates pinpoint the causes of leadership silence. We then discuss the accuracy of subordinates' attributions of leadership silence. Finally, we present the theoretical contributions and managerial implications.